Building Character Through Folklore: Integrating Moral Literacy in Junior High School Reading Journals - Jimat Susilo; Eva Azizah (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2024)
This study explores the role of daily reading journals centered on folklore in fostering moral literacy and character development among junior high school students. Engaging with Indonesian folktales encouraged students to reflect on moral messages and articulate their understanding of values such as respect, honesty, responsibility, and perseverance. Using a qualitative case study approach, data were collected from student journal entries, observations, and educator interviews. The analysis focused on identifying recurring moral themes within the folklore and assessing students’ responses to them in their daily reflections. Findings indicate that regular journal reflections on folklore improve students’ engagement with reading materials and deepen their comprehension of moral concepts embedded in cultural narratives. Through consistent exposure to stories that highlight ethical dilemmas and positive traits, students develop a nuanced understanding of moral values and apply these lessons to their lives. Educators observed increased students' empathy, critical thinking, and awareness of the importance of moral conduct. This study underscores the potential of integrating folklore into school literacy programs as a valuable tool for character education. By situating moral instruction within the culturally relevant context of folklore, schools can make character education more engaging and accessible for students. The research suggests that folklore-based literacy activities could effectively reinforce positive values in educational settings, providing a framework for moral instruction that is both culturally relevant and pedagogically impactful.